Analisis Pengaruh Kualitas Jaringan WiFi terhadap Kegiatan Pembelajaran Mahasiswi Politeknik IDN Bogor - Sandra Murcia Sani; Shafiyyah Shafiyyah; Muhamad Fikri; Ari Ramadhan (Journal of Science, Technology, and Innovation, 2025)
The development of information and communication technology in the era of globalization has brought significant changes in various aspects of life, including education. Technology enables the processing and delivery of information quickly, accurately, and efficiently, but it also poses challenges such as misuse and digital crime. In the context of education, the successful use of technology is highly dependent on the availability of infrastructure, particularly the quality of the internet network. WiFi is one of the main tools that supports access to digital learning materials, but poor network quality can interfere with learning effectiveness. This study aims to analyze the effect of WiFi network quality on the learning activities of female students at the Bogor IDN Polytechnic. The study uses a quantitative approach with data collection through technical network measurements using the Speedtest application and a questionnaire that assesses the students' experience in using WiFi for learning. The sample consisted of 25 female students randomly selected from the population of active female students. The results of this study are expected to provide an understanding of the role of WiFi network quality in supporting learning, as well as a basis for the campus to improve network services so that the learning process becomes more effective and comfortable. This study is in line with previous findings that emphasize the importance of internet access quality for student comfort and learning participation.